Social determinants of health and frailty are associated with all-cause mortality in older adults - Emmanuel González-Bautista (2020)
© 2019, Instituto Nacional de Salud Publica. Objective. To examine the longitudinal association between the social determinants of health (SDH) and frailty status with all-cause mortality in older Mexican adults. Materials and methods. Longitudinal study with a sample of adults aged 60 and over of Study on Global AGEing and Adult Health (SAGE) in Mexico. A Cox proportional hazard model was used to estimate the SDH and frailty-related hazard ratios (HR) for mortality over the study period. Results. Overall mortality rate was 16.9%. Higher education, having a higher frequency of inter-personal contacts (HR=0.96; p < 0.01) reduced the risk of dying, after adjusting for potential confounders. While, not counting on someone to trust (HR= 1.59; p < 0.03) and having a sense a lack of control over important decisions in life increased the mortality risk. Conclusions. Given that frailty and the SDH affect health using independent pathways, public health systems in Mexico could benefit from increasing the capacity of identifying frail and isolated older adults and providing a risk-stratified health care accordingly.